2018
DOI: 10.5530/pj.2018.4.121
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dietary Curcumin and Capsaicin on LPS-Induced Inflammation in Mice

Abstract: Objective:The current study aimed to evaluate the anti-inflammatory potency of combined curcumin and capsaicin against lipopolysaccharide (LPS) induced organ damage in mice. Methods: Adult male albino mice were distributed into five experimental groups for treatment with olive oil, LPS, curcumin, capsaicin and their combination, respectively, for 7 days prior to LPS induced inflammation. At the end of the experiment, blood samples were collected and used for the analysis of serum non-specific enzymes including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The SOD and CAT found to be critical parameters in sepsis; elevation of SOD and CAT caused accumulation of H 2 O 2 in cells. Meanwhile, Vasanthkumar et al [23] reported similar increments in LPO and NO after sepsis induction in mice using LPS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The SOD and CAT found to be critical parameters in sepsis; elevation of SOD and CAT caused accumulation of H 2 O 2 in cells. Meanwhile, Vasanthkumar et al [23] reported similar increments in LPO and NO after sepsis induction in mice using LPS.…”
Section: Discussionmentioning
confidence: 88%
“…Curcumin markedly inhibited hemolysis and lipid peroxidation of erythrocytes induced by linoleate by functioning as a scavenger of NO and blocking its synthesizing enzyme [25]. Curcumin also markedly decreased LPO and NO in the kidney of sepsis-induced mice [23]. C66, a novel curcumin derivative, was reported to reduce TNF-α, IL-1β, COX-2, and NF-κB production, in high glucose-stimulated diabetic rats [43].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effects of capsaicin may be enhanced when used in combination with other spices. One study showed that pre-treatment of mice with a combination of capsaicin and curcumin (the main active ingredient in turmeric) resulted in better protection against LPS-induced inflammation than capsaicin alone (Vasanthkumar et al, 2018). This result highlights the potential beneficial impact of combining spices.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%